Functional pulmonary MRI using hyperpolarised 3He - Ball, Iain Keith (2011)
The microstructure of the lung is complex, containing many branching airways and alveolar sacs for optimal gas exchange. Lung diseases such as cystic fibrosis (CF), asthma, and emphysema lead to a destruction of this microstructure. As such, there is a growing interest in the early identification and assessment of lung disease using non invasive imaging techniques. Pulmonary function tests such as spirometry and plethysmography are currently used for this purpose but can only provide quantitative lung function measurements rather than direct measurements of lung physiology and disease. Computed tomography (CT) has also been used but due to risk of cell damage and mutation from the ionising radiation, long term monitoring of the lungs is severely constrained. Recently, new methods based on magnetic resonance imaging (MRI) have been developed to provide diagnostic imaging of the lung. Conventional MRI is not very well suited for lung imaging due to the very low proton density of the pulmonary airspaces. This problem can be overcome by making the patient inspire noble gases such as 3He whose polarisations have been vastly increased through optical pumping. Therefore 3He MRI permits a non-invasive determination of lung function. The high diffusion coefficient of 3He can be exploited to probe the microstructure of the lung. By measuring how fast 3He diffuses within the lung, the size of the lung microstructure can be assessed. Normally, the airspace walls impede the diffusion of the gas but for diseased lungs where microstructure has been destroyed, diffusion is less restricted and a higher apparent diffusion coefficient (ADC) is observed. The research conducted for this thesis focused on the measurement of ADC using three different MRI pulse sequences with each sequence being designed to assess the peripheral airspaces over different length scales. These sequences were then implemented on three different subject study groups.